The Legal Politics of Combating Online Gambling as a Cybercrime in Indonesia - Andronius Basado Siahaan; Ismaidar Ismaidar; Alberto Paskah Tarigan; Bima Agung Wibowo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Online gambling is a form of cybercrime that exploits information and communication technology, particularly the internet, as a medium for committing gambling offenses. Online gambling as a form of cybercrime has become an increasingly widespread phenomenon alongside the rapid development of information and communication technology. In general, Indonesian law prohibits all forms of gambling, whether conventional or online. Gambling, which was previously known only in its conventional form, has now transformed into the digital realm by utilizing the internet as the primary medium. This study aims to analyze the implementation of legal policies in combating online gambling in Indonesia from a legal-political perspective. The study employs a normative legal approach using a literature review method. Data were collected through an examination of various legal materials, such as legislation, books, academic journals, and relevant online sources pertaining to criminal law policies and crime. The data obtained was then analyzed using qualitative descriptive analysis techniques to understand the legal framework governing online gambling and its implementation in law enforcement practices. The results of the study indicate that the implementation of legal policies in Indonesia regarding online gambling still faces various challenges and is not yet fully effective. Legal policy plays a significant role in enhancing effectiveness.